Valores personales e interpersonales en adolescentes y adultos de la ciudad de Medellín y el área metropolitana (2009)
In this article are presented the results of an investigation in social psychology that had that objective to evaluate six personal values and six interpersonal vales by using two questionnaires in a sample of 970 people at the city of Medellín and metropolitan area. The main objective of the protect was to determinate if it existed differences among each one of the 12 values among the different socioeconomic stratum. As the most relevant finding of the study it stands out the fact that there were not meaning statistical differences among the statistical value of the means for any of the values in the stratums. The graphical comparison of the weights of the means for each one of the six values tested by each questionnaire (SPV and SIV) didn't evidenced, neither, substantial differences among the Argentinean and Spaniard population related to the Colombian sample: an interesting finding for Tran cultural psychology.